Fate of abstracts presented at an International Commission on Occupational Health (ICOH) congress – followed by publication in peer-reviewed journals? - Rollin, Laetitia; Darmoni, Stefan; Caillard, Jean-François; Gehanno, Jean-Francois (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVES ': 'Presentations at international meetings offer an excellent way to disseminate current research findings. One measure of the quality of research is its subsequent publication. Our study aimed to determine the publication rate of abstracts presented at a congress of the International Commission of Occupational Health (ICOH), and to identify predictive factors of publication and differences between presented abstracts and subsequently published papers. ' ' METHODS ': 'We identified a random sample of 318 abstracts presented at the 2000 ICOH meeting from the book of abstracts. Using Medline and Embase, we assessed their publication rate in the period ranging from 1998 to 2006 and investigated the factors associated with publication rate. ' ' RESULTS ': 'Of 318 abstracts originating from 51 countries, 105 articles [33%, 95% confidence interval (95% CI) 27–38)] were subsequently published in 67 journals indexed in Medline or Embase. Mean time to publication was 17 months (95% CI 13–21). Multivariate analysis revealed that abstracts with quantitative data and written by authors originating from developed countries were significantly more published. From the time of abstract presentation to publication in a peer-reviewed journal, both the study sample size and the first author frequently changed (respectively 25% and 29%), but the overall conclusions remained stable, except in one case. ' ' CONCLUSIONS ': 'Most of the abstracts presented at the 2000 ICOH congress were not subsequently published as full research reports. If this is the case for most abstracts submitted to conferences, this may limit the ability of a reader to judge the validity, reliability, and generalizability of the research presented. Caution is advised when referencing or generalizing from abstracts that have not been subsequently published in full.
Keywords: abstract; bibliometrics; ICOH; International Commission on Occupational Health; journal; peer review; peer-reviewed journal; publication; scientific meeting